A Study on the Effectiveness of Social Media Campaigns in Myntra's Online Marketing Strategy (International Journal of Food and Nutritional Sciences, 2022)
This study examines the effectiveness of social media campaigns in Myntra's online marketing strategy. As a leading e-commerce platform in India, Myntra leverages various social media platforms to enhance brand visibility, engage customers, and drive sales. The study focuses on how these campaigns influence consumer behavior, brand loyalty, and overall sales performance. By analyzing specific social media campaigns, engagement metrics, and sales data, the paper aims to provide insights into the impact of social media on Myntra's business growth. The findings highlight the importance of targeted social media strategies in achieving marketing objectives and recommend optimizing future campaigns.